EFFECTIVENESS OF DIGITAL MARKETING: AS A NEW STRATEGY TOOL FOR VALUE OF CUSTOMER’S SERVICES PERSPECTIVE IN LIBYAN TELECOMMUNICATION INDUSTRY - Omran Elgahwash, Fouad (International Journal of Psychosocial Rehabilitation, 2021)
Digital marketing theories, practices, and models from other industries are adopted an applied to the local communication industry to lay the foundation for making it smart and sustainable. Digital Marketing is growth of online shopping and increase in technological changes business’ future. This paper focuses on Libyan Telecommunications companies-based, in technology changes. The greatest key in today’s technologies is to achieve a balance on both offline and online stores and services, which is possible through customer loyalty and value in the digitalization era. It is not only providing useful insights as customer views and also possible areas of research which could have further value addition in terms of growing in this industry. A descriptive approach is adopted, using an online questionnaire tool to investigate the behavior of respondents on the current digital marketing practices and capabilities of Libyan Telecommunication companies. Today, many Libyan telecom companies attempt to take advantage of digital marketing channels to provide suitable services for customers anywhere to improve their satisfaction level. The population consisted of experts in communications industry to identify most important of digital marketing. In particular, in the era of digital marketing, customers have more media channels to choose from and traditional marketing models affected heavily by Internet- smartphones and social media-based marketing for developing new customer groups or new market segments.